(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
Arbitration’s objectivity, efficiency, and cross-jurisdictional enforceability make it the favoured alternative for business dispute resolution. This study takes a look at arbitration in India through the lens of international trade, comparing it to global frameworks including the ICSID Convention, the UNCITRAL Model Law, and the ICC Rules. This paper examines the legislative mandates, judicial precedents, and institutional policies that have an impact on arbitration in India from a theoretical and methodological perspective. The findings show that Indian law is now much more in line with worldwide best practices as a result of legislative revisions, such as the 2015, 2019, and 2021 modifications to the Arbitration and Conciliation Act, 1996. Inadequate institutional infrastructure, delays in enforcement, and judicial meddling are some of the recurring difficulties that continue to limit efficiency. The paper asserts that in order to establish India as a centre for international trade dispute resolution, it is essential to improve institutional arbitration, implement digital case management, and maintain consistent court support.